ANALYSIS OF DEVELOPMENT PLANNING PERFORMANCE TO INCREASE THE VALUE OF PUBLIC SERVICES: AN ANALYSIS OF THE EVELOPMENT PLANNING PROCESS FOR 2019-2021 AT LEMBATA REGIONAL RESEARCH AND DEVELOPMENT PLANNING AGENCY - Wukak, Maria Fransiska Ure; Supriyono, Bambang; Wike, Wike (Faculty of Administrative Science, Universitas Brawijaya, 2024)
The goal of regional autonomy can be achieved through development, which is preceded by a plan. Therefore, planning becomes the benchmark for the success of a development. This article analyzes the planning performance for the 2019 to 2021 plan years at the Regional Research and Development Planning Agency (Bappelitbangda) of Lembata Regency. This analysis aims to determine the extent to which the outputs produced can be used to produce outcomes that touch more on the aspects and needs of the community and become a consideration for the Head of Bappelitbangda in taking strategic steps to improve planning performance and the value of public services. The measurement of performance indicators at Bappelitbangda uses performance identification criteria according to Mahsun (2006), namely inputs, processes, outputs, outcomes, benefits, and impacts. Measurement and analysis can only be done on input, process, output, and outcome groups. The results of the analysis show that planning performance in Bappelitbangda is still output-focused and not outcome-focused, which is indicated by the unbalanced proportion between the funds spent (inputs) and the outcomes produced. Based on the results of this simple analysis, it is expected that Bappelitbangda needs to carry out strategies for future planning improvements by considering aspects of the composition of the drafting team, work mechanisms, and understanding and meaning of the drafting team towards the importance of planning documents.